Existencial competence (savoir-être) in language learning. Redefinitions, applications, challenges - Smuk, Maciej (Glottodidactica, 2018)
This article deals with the notion of savoir-être (existential competence) and the meanings that can be attributed to it in the teaching of foreign languages. After discussing the most important, sometimes contradictory, definitions and their possible interpretations, we propose our conception of the competence of savoir-être. The categories of savoir-être (4ACS model) are listed, classified and discussed, the sub-competencies that are part of it, its stakes and its relations with other competences qualified as general. The description of the model is accompanied by terminological explanations concerning the impact of individual variables on language learning.